Cure or curd: Modification of lipid profiles and cardio‐cerebrovascular events after hepatitis C virus eradication. Issue 11 (9th July 2020) - Huang, Chung‐Feng; Dai, Chia‐Yen; Yeh, Ming‐Lun; Huang, Ching‐I; Lee, Hsiang‐Chun; Lai, Wen‐Ter; Liang, Po‐Cheng; Lin, Yi‐Hung; Hsieh, Ming‐Yen; Hou, Nai‐Jen; Lin, Zu‐Yau; Chen, Shinn‐Cherng; et al.
Abstract: Hepatitis C virus (HCV) eradication deteriorates lipid profiles. Although HCV eradication may reduce the risk of vascular events as a whole, whether deteriorated lipid profiles increases the risk of cardio‐cerebral disease in certain patients is elusive. Serial lipid profiles were measured before, during, at and 3 months after the end of direct‐acting antivirals (DAAs) therapy, and annually thereafter in chronic hepatitis C patients who achieved a sustained virological response (SVR, undetectable HCV RNA at posttreatment week 12). The primary end‐point was the occurrence of the events. A total of 617 patients were included, with a mean follow‐up period of 26.8 months (range: 1‐65 months). The total cholesterol and low‐density lipoprotein cholesterol (LDL‐C) levels increased significantly from treatment week 4 to 2 years after treatment. Logistic regression analysis revealed that the factors independently associated with a significant cholesterol increase included age (odds ratio [OR]/95% confidence intervals [CIs]:1.02/1.006‐1.039, P = .007) and smoking (OR/CI:3.21/1.14‐9.02, P = .027). Five patients developed cardio‐cerebral diseases during 1376 person‐years follow‐up period. Compared to patients without vascular events, a significantly higher proportion of those with vascular events experienced an LDL‐C surge >40% (80% vs 19.9%, P = .001). Cox‐regression analysis revealed that an LDL‐C surge >40% was the only factor predictive of vascular events (HR/CI: 15.44/1.73‐138.20, P = .014). Dyslipidemia occurred after HCV eradication, and it was associated with the risk of cardio‐cerebrovascular diseases. Attention should also be paid to the extrahepatic consequence beyond liver‐related complications in the post‐SVR era.